2018
DOI: 10.1177/0961203318776109
|View full text |Cite
|
Sign up to set email alerts
|

Histological predictors of renal outcome in lupus nephritis: the importance of tubulointerstitial lesions and scoring of glomerular lesions

Abstract: Introduction Lupus nephritis (LN) affects nearly 60% of patients with systemic lupus erythematosus and up to 30% of them will progress to end-stage renal disease (ESRD), despite receiving aggressive immunosuppressive therapy. The prognostic value of ISN/RPS classification is controversial. Therefore, we aimed to identify clinical and pathological predictors of outcome in LN patients independent of this classification. Material and methods Thirty-seven patients with LN who underwent percutaneous kidney biopsy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 34 publications
2
37
0
1
Order By: Relevance
“…In comparison to other studies, the patients responded to treatment in less time and proteinuria recovery happened earlier in this study (3,6,12). Similar to our research, recovery from proteinuria was de ned as proteinuria < 0.5 g/24 h in the study of Touma Z in 2014 (7).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In comparison to other studies, the patients responded to treatment in less time and proteinuria recovery happened earlier in this study (3,6,12). Similar to our research, recovery from proteinuria was de ned as proteinuria < 0.5 g/24 h in the study of Touma Z in 2014 (7).…”
Section: Discussionsupporting
confidence: 80%
“…The reason for this discrepancy is that the recovery time was differently accomplished between the two studies in other hand; Touma et al registered proteinuria recovery only if happened twice respectively whereas in our study one-time proteinuria < 0.5 g in 24 hours was little enough to categorize patients as recovered from proteinuria. Also in this research the only criteria for protein loss in urine was a 24-hour urine analysis measuring proteinuria but Touma et al have used dip stick or spot ratio of urine creatinine if they did not have access to 24-hour urine samples (6). Hernandez et al (22) showed more similar results with study in which 69% of patients after 6 months and 86% after 12 months of treatment beginning were recovered from proteinuria.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…17 18 Tubulointerstitial lesions, such as interstitial fibrosis and tubular atrophy, are associated with poor outcome. [19][20][21] A revision of the 2003 ISN/RPS classification has recently been proposed and awaits endorsement. 22…”
Section: Pathological Assessment Of Kidney Biopsymentioning
confidence: 99%